1981
DOI: 10.1029/ja086ia07p05751
|View full text |Cite
|
Sign up to set email alerts
|

Height and latitude structure of electric fields and currents due to local east‐west winds in the equatorial electrojet

Abstract: Using the equivalent electrical circuit method for the theoretical treatment of the local wind effects on the equatorial electrojet, the height structures of electric fields and currents that are generated by height‐varying east‐west winds in the electrojet region have been calculated for theoretical model wind sturctures and for a variety of experimentally observed wind structures. The results bring out clearly the nature and extent of the local wind effects on the height and latitude structures of the equato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 54 publications
6
52
0
Order By: Relevance
“…Apart from the general characteristics of E sb layers and that of VHF radar returns from them being different during solar minimum and maximum periods, certain other important aspects of the dominant physical processes controlling the growth processes of the gradient instabilities under varying solar activity conditions also appear to emerge from the present investigation. Some of the cases of radar returns from the E sb layers that are illustrated in the previous sections show that the velocity profiles of the type II irregularities associated with E sb layers show the presence of large velocity shears (Reddy and Devasia, 1981). As the occurrence of E sb layers are in general associated with very weak (almost zero) east-west electric field, these velocity shears in the Doppler velocity profiles are equivalent to wind shears.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from the general characteristics of E sb layers and that of VHF radar returns from them being different during solar minimum and maximum periods, certain other important aspects of the dominant physical processes controlling the growth processes of the gradient instabilities under varying solar activity conditions also appear to emerge from the present investigation. Some of the cases of radar returns from the E sb layers that are illustrated in the previous sections show that the velocity profiles of the type II irregularities associated with E sb layers show the presence of large velocity shears (Reddy and Devasia, 1981). As the occurrence of E sb layers are in general associated with very weak (almost zero) east-west electric field, these velocity shears in the Doppler velocity profiles are equivalent to wind shears.…”
Section: Discussionmentioning
confidence: 99%
“…As the occurrence of E sb layers are in general associated with very weak (almost zero) east-west electric field, these velocity shears in the Doppler velocity profiles are equivalent to wind shears. The presence of an E sb layer under the background conditions of a very weak east-west electric field and large shears in the Doppler velocity profiles of the type II irregularities associated with it suggest to the existence of highly structured wind-induced polarization electric field generated by the height varying zonal winds in the EEJ region (Reddy and Devasia, 1981). Some of the Doppler velocity profiles shown in the present studies have a close similarity to the reversal of drift velocity with height as shown by Reddy (1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, the thresh old value will be up-shifted when the wind field is par al lel to the elec tron drift ve loc ity, and con versely, the thresh old will be down-shifted when wind field is anti-par al lel to the elec tron drift ve loc ity. More over, past ob ser va tions and model cal cu la tions of neu tral wind in the equa to rial E re gion (e.g., Reddy and Devasia 1981;Larsen and Odom 1997;Hysell et al 2002) in di cate that the hor i zon tal wind field is mostly par al lel to the di rec tion of drift ve loc ity. If thresh old drift ve loc ity is not up-shifted by par al lel neu tral wind, and re mains the same at near the ion acous tic ve loc ity, then two-stream ) for that col umn, while the la bels on the left give k z (in m -1 ) for that row.…”
Section: Sum Mary and Discussionmentioning
confidence: 99%